Culture and the Non-Human World in Crisis (KULT_online, 2018)
In her monograph Ecology without Culture – Aesthetics for a Toxic World, literary scholar Christine Marran calls for a reconsideration of the role that culture can play in the current ecological crisis – both through cementing ethno-nationalist imaginations of the natural world and their subversion. Through an analysis of mostly Japanese literature and film, the author shows how certain biotropes (images and metaphors that point toward the natural world) and aestheticizing of non-human scales and perspectives can lead to a more environmentally engaged form of culture. Marran imagines literary studies that are attuned to the challenges of the more-than-human material world and throughout her book develops exemplary multi-layered analyses of primary texts.